2006
DOI: 10.1002/cyto.b.20144
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CD38 expression on peripheral blood T‐cells and monocytes, and response to antiretroviral therapy: A one‐year longitudinal study of a cohort of chronically infected ART‐naive HIV‐1+ patients

Abstract: Background: HIV-1 infection has been associated with high expression of CD38 on peripheral blood (PB) CD81 and CD41 T-cells, which has been related with poor prognosis in untreated HIV-11 patients. In turn, CD38 expression on PB monocytes from HIV-11 individuals and its behavior after starting antiretroviral therapy (ART) have been poorly studied.Methods: CD38 expression on PB CD81 and CD41 T-lymphocytes and monocytes was prospectively analyzed in 30 ART-naive HIV-11 patients, using a quantitative multiparamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
(61 reference statements)
1
26
0
Order By: Relevance
“…CD38, the most extensively studied activation marker in HIV-1-infected subjects, had been reported to be upregulated on CD8 + T cells in association with disease progression [12-14,35-38]. The degree of correlation between CD38 expression on CD8 + T cells and HIV-1 plasma viral load in our study was moderate but comparable to other African studies [12,14].…”
Section: Discussionsupporting
confidence: 86%
“…CD38, the most extensively studied activation marker in HIV-1-infected subjects, had been reported to be upregulated on CD8 + T cells in association with disease progression [12-14,35-38]. The degree of correlation between CD38 expression on CD8 + T cells and HIV-1 plasma viral load in our study was moderate but comparable to other African studies [12,14].…”
Section: Discussionsupporting
confidence: 86%
“…HAART has been shown to correct much of the inflammation induced by HIV at the level of CD4+ and CD8+ T cells [31]. Abnormalities in a number of serum markers have been shown to improve but not resolve on HAART [32, 33], so it was of interest to see if these changes extended to a broader panel of soluble mediators of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported higher circulating levels of proinflammatory cytokines and monocyte activation in various cohorts of HIV-infected patients treated for a maximum of 2 years and with inclusion criteria for the plasma viral load that were higher than in our study. [33][34][35][36][37][38][39] These less strict viral load criteria suggest the possibility of incomplete viral suppression. The data obtained from our HIV cohort (median treatment duration, 9.4 years/viral load < _20 RNA copies/mL) suggest that a longer duration of ART and consequently of viral suppression can restore some HIV-associated immunologic abnormalities, such as increased proinflammatory cytokine levels and monocyte hyperactivation.…”
Section: Discussionmentioning
confidence: 96%